Environmental Determinants and Spatial Distribution of Pediatric Pneumonia in Padang City - Maharani, Diva; Masrizal, Masrizal; Novirsa, Randy; Pradipta, Yudi (UNIVERSITAS ALIFAH PADANG, 2026)
Background: Pneumonia remains the leading infectious cause of death in children under five globally. In Padang City, Indonesia, pediatric pneumonia cases increased sharply from 2021 to 2023, yet the environmental and host-related determinants driving this trend remain poorly understood in the local tropical urban context.Objective: This study aimed to analyze the correlation between physical environmental factors humidity, wind speed, temperature, rainfall, PM10, and PM2.5 and pediatric pneumonia incidence in Padang City from 2021 to 2023, and to spatially map host-related intervention coverage across sub-districts.Methods: An ecological study design was employed using monthly secondary data aggregated at the city level (n = 36 months). Pneumonia case data were obtained from the Padang City Health Office, meteorological data from BPS, and air quality data from the Environmental Agency. Pearson correlation and multiple linear regression were used for statistical analysis following assumption testing. Spatial overlay mapping was conducted using QGIS to examine the geographic distribution of cases in relation to exclusive breastfeeding, vitamin A supplementation, and complete basic immunization coverage.Results: A total of 5,428 cases were recorded (mean: 150.78 cases/month). Wind speed showed a significant positive correlation (r = 0.436, p = 0.008) and PM2.5 a significant negative correlation (r = −0.516, p = 0.003) with pneumonia incidence. PM2.5 was the most dominant predictor (R² = 0.463). Spatial analysis identified Kuranji and Lubuk Begalung as persistently high-burden sub-districts, consistently associated with inadequate host-factor intervention coverage.Conclusion: Wind speed and PM2.5 are significant environmental determinants of pediatric pneumonia in Padang City. Integrated strategies combining air quality monitoring, vitamin A supplementation, immunization programs, and strengthened Posyandu-based interventions are essential to reduce pneumonia burden in tropical urban settings.